2017
DOI: 10.1038/srep46554
|View full text |Cite
|
Sign up to set email alerts
|

High pesticide risk to honey bees despite low focal crop pollen collection during pollination of a mass blooming crop

Abstract: Honey bees provide critical pollination services for many agricultural crops. While the contribution of pesticides to current hive loss rates is debated, remarkably little is known regarding the magnitude of risk to bees and mechanisms of exposure during pollination. Here, we show that pesticide risk in recently accumulated beebread was above regulatory agency levels of concern for acute or chronic exposure at 5 and 22 of the 30 apple orchards, respectively, where we placed 120 experimental hives. Landscape co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
79
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(91 citation statements)
references
References 51 publications
9
79
2
1
Order By: Relevance
“…We identified a total of 44 insecticide exposures (30 case, 14 control) and only 10 fungicide exposures (7 case, 3 control) in our dataset. These findings agree with a recent study that demonstrated how bees sampled from the field are more likely to be exposed to insecticides encountered through diverse foraging of wildflowers and other pollen sources (non-focal crop pollen) than fungicides which dominate focal crop pollen foraging 43 .…”
Section: Discussionsupporting
confidence: 92%
“…We identified a total of 44 insecticide exposures (30 case, 14 control) and only 10 fungicide exposures (7 case, 3 control) in our dataset. These findings agree with a recent study that demonstrated how bees sampled from the field are more likely to be exposed to insecticides encountered through diverse foraging of wildflowers and other pollen sources (non-focal crop pollen) than fungicides which dominate focal crop pollen foraging 43 .…”
Section: Discussionsupporting
confidence: 92%
“…The LD 50 values (Table S1) of fipronil, ethiprole, endosulfan and abamectin were obtained from published data and IC 50 values were determined in the present study. The binding free energy from molecular docking and inhibition of AmRDL measured from electrophysiology exhibited high correlation with a value of 0.7071 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, acetamiprid and dinotefuran showed similar median lethal doses, and high toxicities to Osmia excavata Alfke, as did dimethoate to A. mellifera . In addition, fluralaner exhibited a similar toxic level to abamectin (0.03 μg adult −1 ), fipronil (0.0038 μg adult −1 ), and ethiprole (0.019 μg adult −1 ) . In China, ethiprole and flufiprole have been widely used for pest control in rice fields in preference to fipronil due to their lower toxicity to fish, even though both of them also have high toxicity to honeybees (Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…Systemic insecticides are taken up by plant tissues and can remain active for long 238 periods. Indeed, a major route of exposure for foraging bees to neonicotinoids and other 239 pesticides through nectar and pollen obtained from flowering weeds in agricultural areas, where 240 the weeds have taken up residues from the soil (37)(38)(39). Seed treatments likely exacerbate this 241 route of exposure, since neonicotinoids can remain present in the soil for years; indeed, recent 242 studies identified imidacloprid residues in plants and bee colonies, though imidacloprid use had 243 been discontinued in these study regions in previous years (37,40).…”
Section: Discussion 200mentioning
confidence: 99%